2018
DOI: 10.1515/ats-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphometry of the brainstem of the male and female Helmeted Guinea Fowl (Numida meleagris)

Abstract: The aim of this study was to obtain base-line morphometric data on the whole brain and brainstem in the adult male and female helmeted guinea fowl (Numida meleagris), and compare the result in the two sexes. Brain samples of seventy adult helmeted guinea fowls, comprising 35 males and 35 females, intended for slaughter, were extracted for the study. The body weights for both male and female helmeted guinea fowls were 1247 ± 5.51 g and 1230 ± 4.85 g, respectively. The mean brain weights were 3.39 ± 0.02 g and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This was found to be different and specific to this species as bony protuberances rarely occurred on top of the skull and are mainly restricted to the beak. This process which is a projection from the frontal bone is popularly called the ‘helmet’ (Adam et al, 2018) which has shown in this study to be made entirely of the frontal bone. This process did not form part of the cranial cavity, meaning that the brain does not extend into it since it is not hollow.…”
Section: Discussionmentioning
confidence: 94%
“…This was found to be different and specific to this species as bony protuberances rarely occurred on top of the skull and are mainly restricted to the beak. This process which is a projection from the frontal bone is popularly called the ‘helmet’ (Adam et al, 2018) which has shown in this study to be made entirely of the frontal bone. This process did not form part of the cranial cavity, meaning that the brain does not extend into it since it is not hollow.…”
Section: Discussionmentioning
confidence: 94%
“…the digestive system [14,31], reproductive system [2,11], respiratory system [5,15], integuments [29,41,45], nervous system [3], muscular system [9] and forelimb skeleton [1]. Generally, studies on forelimb anatomy of avian species abound, probably due to the relevance of the forelimb to flight.…”
Section: Introductionmentioning
confidence: 99%